Full genome sequence of the Western Reserve strain of vaccinia virus determined by third-generation sequencing - Prazsák István (GENOME ANNOUNCEMENTS, 2018)
The vaccinia virus is a large, complex virus belonging to the Poxviridae family. Here, we report the complete, annotated genome sequence of the neurovirulent Western Reserve laboratory strain of this virus, which was sequenced on the Pacific Biosciences RS II and Oxford Nanopore MinION platforms.